2010
DOI: 10.1038/onc.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cɛ mediates Stat3Ser727 phosphorylation, Stat3-regulated gene expression, and cell invasion in various human cancer cell lines through integration with MAPK cascade (RAF-1, MEK1/2, and ERK1/2)

Abstract: Protein kinase C epsilon (PKCε), a novel calcium-independent PKC isoform, has been shown to be a transforming oncogene. PKCε-mediated oncogenic activity is linked to its ability to promote cell survival. However, the mechanisms by which PKCε signals cell survival remain elusive. We found that signal transducers and activators of transcription 3 (Stat3), which is constitutively activated in a wide variety of human cancers, is a protein partner of PKCε. Stat3 has two conserved amino acid (Tyr705 and Ser727) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…Signal transducers and activators of transcription 3 (Stat3) activation by PKC in glioma cells also stimulate cell invasion. These responses are found in not only glioma, but also several additional types of human cancer cells, including prostate, skin (melanoma), bladder, colon, lung, pancreatic, and breast [208]. Furthermore, galectin-1, a homodimeric adhesion molecule, is linked with the trafficking of 1-integrin, which is controlled by a PKC /vimentindependent pathway.…”
Section: Gastrointestinal Stromal Tumormentioning
confidence: 99%
“…Signal transducers and activators of transcription 3 (Stat3) activation by PKC in glioma cells also stimulate cell invasion. These responses are found in not only glioma, but also several additional types of human cancer cells, including prostate, skin (melanoma), bladder, colon, lung, pancreatic, and breast [208]. Furthermore, galectin-1, a homodimeric adhesion molecule, is linked with the trafficking of 1-integrin, which is controlled by a PKC /vimentindependent pathway.…”
Section: Gastrointestinal Stromal Tumormentioning
confidence: 99%
“…This notion is supported by studies in other cell types showing that novel PKC isoforms, such as PKC␦ and PKC⑀, can target this residue in STAT3. [38][39][40]50 Moreover, one study has demonstrated that PKC activation of CLL cells stimulates Mcl-1 expression, 51 and our own work indicates that PKC␦ and PKC⑀ are highly expressed in CLL cells. 26 In the present study, stimulation of CLL cells with bryostatin induced increased levels of pS 727 -STAT3 and Mcl-1 protein expression that was dependent on STAT3 activation; treatment of CLL cells with a STAT3 inhibitor before bryostatin stimulation inhibited induction of STAT3 phosphorylation and Mcl-1 expression.…”
Section: Discussionmentioning
confidence: 78%
“…[38][39][40] To investigate whether PKC is similarly involved in the regulation of Mcl-1 expression in CLL cells, we examined the effect of PKC inhibition on pS 727 -STAT3 levels and Mcl-1 expression. Figure 6A Figure 6C shows that IL-6R blockade had a small, but significant, additive effect on the inhibition of Mcl-1 expression when used in combination with BisI.…”
Section: Induction Of Ps 727 -Stat3 In Cll Cells By C-abl and Nf-b Rementioning
confidence: 99%
“…CTRP8‐RXFP1 is emerging as a new ligand–receptor system which promotes GBM migration (Glogowska et al ., 2013) and, as shown here, protects against the cytotoxic effects of the DNA alkylating drug TMZ. Likely initiated by an interaction of RXFP1 with the small G protein Gα i3 to activate the Gα i3 ‐Gβγ‐PI3K signaling pathway (Nguyen and Dessauer, 2005), our discovery of a novel CTRP8‐RXFP1‐STAT3 signaling cascade in human GBM links this CTRP8‐RXFP1 system to oncogenic STAT3 functional outcomes, including GBM cell survival, angiogenesis, and cell migration/invasion (Aziz et al ., 2010; Butler et al ., 2013; Ouedraogo et al ., 2017). CTRP8‐activated RXFP1 may utilize PI3K to mediate STAT3 activation as PI3K and its target BMX TEC kinase were recently shown to mediate the phosphorylation of STAT3 (Glogowska et al ., 2013; Hart et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%